ACSIS Atlantic Ocean medium resolution SST dataset: Reconstructed 5‐day, ½‐degree, Atlantic Ocean SST (1950‐2014). (11th July 2020) - Williams, Simon David Paul; Berry, David I.
Abstract: A new dataset, the ACSIS Atlantic Ocean medium resolution SST dataset, is presented. This new dataset spans the period 1950–2014 at a 5‐day, ½‐degree resolution and covers the Atlantic Ocean. The dataset is based on in situ sea surface temperature (SST) observations from the International Comprehensive Ocean‐Atmosphere Data Set interpolated using Kriging to infill gaps and is available from the Centre for Environmental Data Analysis (CEDA) archive. Compared to existing datasets, the resolution is increased by a factor of 4 spatially and 6 temporally. Abstract : Mean SST anomaly for 26–30 March 1952 from the new ACSIS Atlantic Ocean medium resolution SST dataset.